Preservice Teachers’ Knowledge Levels, Risk Perceptions and Intentions to Use Renewable Energy: A Structural Equation Model - Mehmet Demirbag; Sirin Yilmaz (Journal of Education in Science, Environment and Health)
In today’s world, energy consumption constitutes a topic on countries’ main agendas. In parallel with the military, technological and scientific developments associated with the increasing population, countries are generating policies that highlight energy sources that play a part in global competition. As with many innovations, factors such as the public’s knowledge levels regarding the innovations, social acceptance, attitudes, intentions and risk perceptions are seen to be directly related to the use of renewable energy. For this reason, the aim of this study was to test the relationships among the knowledge levels, risk perceptions and intentions of preservice teachers regarding renewable energy sources using structural equation model analysis. 642 preservice teachers studying in 3rd and 4th grades, and selected by convenience sampling, participated in the study. According to the results of the structural equation model analysis, the knowledge levels of the preservice teachers related to renewable energy sources negatively predicted their risk perceptions regarding renewable energy sources. Furthermore, while individuals’ risk perceptions negatively predicted some of the theory of planned behavior components related to renewable energy sources, the theory of planned behavior components related to attitude, subjective norms and perceived behavioral control positively predicted the intention to use renewable energy sources. These analyses related to the structural equation model findings are discussed in detail.